PERFORMANCE SIMULATION AND ANALYSIS OF KERRIGHED SSI MULTICORE CLUSTER IN RUNNING A PARALLEL PROGRAM FOR ONLINE INTERACTIVE APPLICATION SERVER - NARENDRA (NIM: 13204166), ASKA
In this final project, computer cluster will be built for the purpose of simulating the performance SSI Kerrighed cluster as an online interactive aplication server. Cluster will be constructed under Linux Debian 5.0 operating system on heterogenous network of workstations with the usage of 5 computers. Before the simulation, Kerrighed's performance as a Single System Image (SSI) will be tested first. Being an SSI cluster, Kerrighed will be tested whether it could give some kind of performance improvement to the cluster in doing a computation process if there is also an elevation in the number of cluster's core processor. Many cluster configuration scenario will be used in this preliminary test. The simulation will be carried by giving different kinds of processes simultaneusly to the computer cluster that could represent the activity of an online interactive aplication server. The processes that will be used on this computer cluster are computation, data save/load, backup, and incoming request. The computation process that will be used is parallel matrix multiplication program, where parallel execution of said program on the cluster will be possibly made by the existence of MPI programming language environment. Many of Kerrighed's capabilities will be used to see whether Kerrighed could effectively distribute its processing session at the simulation so that Kerrighed SSI cluster's effectivity as an online interactive aplication server could be evaluated. The preliminary test's result shows that Kerringhed has an increase performance when the number of the core processor also increase, with an exception if the runned program has low memory consumption then the time needed for the program to distribute the process to all cores longer than to run the particular program. The simulation's result shows that Kerrighed is capable of being a good online interactive application server, although it still has the same problem as other common online interactive application server.